Propagandas da campanha eleitoral a prefeito de Cuiabá do segundo turno de 2012 : aspectos discursivos - Conceição, Rosineide Maria da (2014)
This study was conducted within the scope of the Master Program in Language Studies, in the Research Line “Textual and discursive practices: multiple approaches”. It sought to disentangle the discourse(s) which permeated the campaign for mayor of Cuiabá in 2012, as it is made public in the Free-time Political Propaganda on television (hereinafter HGPE/TV), in the second round, disputed by Mauro Mendes, affiliated to the Brazilian Socialist Party (PSB) and Ludio Cabral, affiliated to the Workers’ Party (PT). It aimed to: apprehend the interdiscursive relationships which permeated the HGPE/TV advertisements; understand how the political advertisements were crafted as enunciation scenes (enclosing scene, generic scene and scenography); understand how the ethos of the enunciator participates in the construction of the scenography; discuss specificities of the political debate in the HGPE/TV. Such objectives have not exhausted the possibilities of study that this object offered, but it is what was presented as achievable at the time. It was an archival research, with the difference that it was possible to observe the file in the making, by following day by day what was being broadcast by the HGPE/TV to the population of Cuiabá, among those the electors that could make one or the other winning candidate. The study was marked by the Discourse Analysis (DA) of the French strand, using the following concepts: interdiscourse, polemic, enunciation scenes (enclosing scene, generic scene and scenography) and ethos. The concepts explored in the dissertation were addressed mainly in the company of Dominique Maingueneau, a discourse analyst of the French school that has shown the fruitfulness of this interpretative paradigm in the reading of any type of statements, including multimodal statements as are the utterances of the HGPE/TV. The analysis showed the controversy around the “alignment”, an argument of campaign claimed by the PT candidate and rebutted by that of the PSB, as well as in relation to “administrative competence”, claimed by the PSB candidate and rebutted by the PT candidate.